1973
DOI: 10.1111/j.1755-3768.1973.tb03802.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Oscillatory Potentials of the Human Electroretinogram in Light and Dark Adaptation

Abstract: The effect of adaptation to short flashes of light on the oscillatory potentials and the slow potentials (a-and b-wave) of the human ERG as well as the effect on adaptometric visual threshold in response to a series of three flashes were studied. The total energy and the dominant frequency of the oscillatory potentials in response to the third (stimulus) flash were calculated by a combined impulse response and Fourier analysis when the interval between the flashes changed and the intensity of the first two (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…In humans, the adult, photopic ERG contains fewer wavelets compared to the scotopic one (Wachtmeister 1972). In the present study using very short ISIs, 0, was found to be attenuated and 0, and 0, not to be recordable in the mature animal.…”
Section: Maturation Of the Opsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the adult, photopic ERG contains fewer wavelets compared to the scotopic one (Wachtmeister 1972). In the present study using very short ISIs, 0, was found to be attenuated and 0, and 0, not to be recordable in the mature animal.…”
Section: Maturation Of the Opsmentioning
confidence: 99%
“…The oscillatory potentials (OPs) of the electrore-6 tinogram (ERG) reflect rapid adaptational changes and represent neuronal activity in the inner part of the retina (Algvere & Westbeck 1972;Wachtmeister 1972;Wachtmeister & Dowling 1978;Heynen et al 1985). Recently it has been reported that the postnatal development of the OPs generated during relatively more photopic conditions is slower compared to the OPs induced during relatively more scotopic conditions (el Azazi 8c Wachtmeister 1990).…”
mentioning
confidence: 99%
“…Thus, the behaviour of the OPs induced at IS1 30 sec entailed photopic qualities at individual levels, but when summated conformed to a scotopic course of postnatal maturation. This may not be a surprising finding as the OPs have been sug gested to represent both scotopic and photopic mechanisms, probably an interaction between the two in the inner retina (Wachtmeister 1972(Wachtmeister , 1974Stodtmeister 1973), and also because the studied range of adaptation was a relatively mesopic one.…”
Section: Maturationmentioning
confidence: 80%
“…5A and B). Thus, contrary to the human OPs, the oscillations in the mature rat retina seem not to be augmented by relatively mesopic conditions (Wachtmeister 1972). This could probably be explained by the rat having considerably fewer cones compared to the human retina, and therefore much more intense light stimulation seems to be needed to elicit optimal OPs.…”
Section: Maturationmentioning
confidence: 94%
See 1 more Smart Citation